Odpowiedzi

2009-10-11T11:28:36+02:00
A) 49 - x2
b) x2 + 1/4
c) 4x2 + 16
d)9x + 64
e+ 1/16x2 + 64
2009-10-11T11:30:53+02:00
A) (7-x)² = 7² -2*7*x + x²=49 -14x+x²
b)(x+1/2)²=x²+2*x*1/2+(1/2)²=x²+x+1/4
c)(2x+4)²=(2x)²+2*2x*4+4²=4x²+16x+16
d)(3x+8)²=(3x)²+2*3x*8+8²=9x²+48x+64
e)(1/4x+8)²=(1/4x)²+2*1/4x*8+8²=1/16x²+4x+64
Pozdrawiam;)
2009-10-11T11:31:30+02:00
A) (7-x)2(kwadrat) = 49-14x+x2(kwadrat)
b) (x+1/2)2=x2(kwadrat)+x+1/4
c) (2x+4)2= 4x2(kwadrat)+ 16x+16
d) (3x+8)2= 9x2(kwadrat)+ 48x+64
e) (1/4x+8)2= 1/16x2(kwadrat) + 4x + 64